Effects of interactive education with conversation map on foot care behaviors in elderly diabetic patients with high-risk diabetic foot - Yingli, Zhang (International Journal of Research in Medical Sciences, 2021)
Background: Diabetic foot is one of the main reasons that seriously affect the quality of life and disability. Good foot care can prevent 85% amputation of diabetic foot patients. The purpose of this study is to explore the effects of interactive education with conversation map on foot care behaviors among elderly diabetic patients with high-risk diabetic foot. Methods: 96 elderly diabetic patients in Endocrinology Department of the Second Affiliated Hospital of Shandong First Medical University from January to December in 2020 were selected as the research objects. According to the parity of the last two digits of the hospitalization number, the odd number was divided into the control group and the even number was divided into the experimental group. The control group was given traditional health education and interactive education with conversation map for diabetic foot launched by the international diabetes federation was added to the experimental group. After 3 months of intervention, fasting blood glucose, 2 hours postprandial blood glucose, glycosylated hemoglobin and foot care behaviors of the two groups were observed. Results: The fasting blood glucose, 2 hours postprandial blood glucose, glycosylated hemoglobin and foot care behaviors of the experimental group were significantly better than those of the control group and the difference was statistically significant (p<0.05). Conclusions: The interactive education with conversation map can effectively improve the foot care behaviors of elderly diabetic patients with high-risk diabetic foot, and then prevent the occurrence of diabetic foot.